ผลกระทบของโลจิสติกส์การท่องเที่ยวต่อความภักดีของนักท่องเที่ยวในจังหวัดแพร่ - มะลิวัลย์ ปินนะ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
This independent research aims to study the traveler's satisfaction for the element of tourism logistics and the impact of tourism logistics on loyalty of tourists in Phrae Province. The samples are 400 tourist randomly selected from visitors that travel to Phare province. Questionnaires are applied for the data collection. The data collection is also analyzed by using Likert Scale for studying the traveler's satisfaction for the element of tourism logistics and the impact on the travelers’ mind in their decision to revisit Phare. Plus, Structural Equation Model: SEM is also applied in the analysis to discover the impact of tourism logistics on loyalty of tourists in Phrae Province. The study reveals that most of the respondents are less than 30 years-old female, single, with Bachelor’s degree. They are the officer or government officer with the salary less than 15,000 baht per month. Moreover, they have been visited Phrae less than 3 times per year, They were informed about travelling information from their friends and decided to travel by themselves with their private vehicle. However, they cannot decide that they will revisit Phare in the future or either recommend to others, yet. The results from Likert Scale reveal that there are several factors which affect the travellers to revisit Phrae. The first factor is physical factor-the road during the journey in Phare (37.25%), followed by the informative factor- guide post (35.35%). Plus, financial factor- Automatic Teller Machine location (33.75%), followed by the public utility- Internet WIFI 3G (32.75%). Moreover, the permanent factor-good materials (34.25%), seducing travelling place-Cultural and historical travelling places (35.50%), the convenient journey- the highway between provinces (36.25%), the convenient basic public utility and hospital (33.50%), Clean motel with appropriate price (34.50%), and cultural festivals (38.50%). For the impact of tourism logistics on loyalty of tourists in Phrae Province which is analyzed by Structural Equation Model: SEM with R program, the analysis got PIFFS ~ FiveA ~ Loyalty as a model. The result reveals that the data are related in the same way. The relations between PIFFS factors which have effect on FiveA including, the guide post, waste segregation, ATM (the amount of ATM in Phrae) 0.641 in lever 0.01 significance of statics. To illustrate, if the PIFFS variable increase 1 unit, FiveA factor will increase 0.641 units. Finally, FiveA factor that has effect on the loyalty of tourists in Phrae including, natural study-walking activity, national park, motel with appropriate price, and natural travelling places such as waterfall and mountain 0.489 in lever 0.01 significance of statics. To illustrate, if the FiveA factor increase 1 unit, the loyalty of tourists in Phrae will increase 0.489 units.